1978
DOI: 10.1136/jech.32.2.131
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of blindness in an Indian rural community.

Abstract: A house-to-house survey of blindness in an Indian rural community covering a population of 20 134 in 12 villages revealed a prevalence rate of 35 blind and 144 partially blind persons per 10 000 population. Blindness was significantly associated with the age, sex, marital status, occupation, and socioeconomic status of the respondents. Caratact, glaucoma, smallpox and trachoma were the main causes of blindness. Preventive measures can reduce the toll of blindness in such a community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…In Africa, the prevalence of scabies was 35.6% in Lilongwe, Malawi 2 and the same figure was reported from Lusaka, Zambia, 12 but a lower prevalence rate (approximately 2%) was found in Gambia 5 . The lower prevalence rate in our study and that reported from Gambia, 5 compared with other studies, 2–4 , 10–12 might be attributable to racial factors, differences in hygiene practices, economic status, or differences in social attitudes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In Africa, the prevalence of scabies was 35.6% in Lilongwe, Malawi 2 and the same figure was reported from Lusaka, Zambia, 12 but a lower prevalence rate (approximately 2%) was found in Gambia 5 . The lower prevalence rate in our study and that reported from Gambia, 5 compared with other studies, 2–4 , 10–12 might be attributable to racial factors, differences in hygiene practices, economic status, or differences in social attitudes.…”
Section: Discussionsupporting
confidence: 70%
“…Scabies is a highly contagious disease caused by the mite Sarcoptes scabiei var hominis . The disease is seen in all socioeconomic groups and communities throughout the world; 1 however, the prevalence of scabies varies widely from one country to another; 2 for example, in some developing countries, the prevalence has been reported to be between 5.8% 3 and 83% 4 among the rural population. Epidemiologic studies performed in underdeveloped countries in Africa also showed great variations.…”
Section: Introductionmentioning
confidence: 99%
“…People from lower socioeconomic groups use eye care services less frequently, although the prevalence of visual impairment and blindness is higher in these groups (Srivastava & Verma 1978;Dana et al 1990;Tielsch et al 1991;Salive et al 1992;Klein et al 1994;Dandona et al 1999Dandona et al , 2001bDandona et al , 2002aDandona et al , 2002bSchaumberg et al 2000;Dandona & Dandona 2001;Ho & Schwab 2001;Michon et al 2002;Munoz et al 2002). Socioeconomic differences are also observed in glaucoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…For TT stage; few lashes can be managed by hyfrecation, radiofrequency epilation or cryotherapy where as Bilamellar tarsal rotation is the surgical procedure of choice, when multiple lashes are involved and in experienced hands it has an overall success rate of 80% [4].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of trachoma has decreased from 71.07% in 1977 [3], when it was among the top five cause of blindness in India to 8.5 % in 1998 due to active intervention from both government and non government organizations under the agesis of National Programme for Trachoma Control (NPTC), which was launched in 1963 [4,5]. The recognization, that trachoma is a major cause of blindness lead to NPTC even before national programme of control of blindness, which was launched in 1976.…”
Section: Discussionmentioning
confidence: 99%